Sztuka religijna dawniej i dziś - Wędrówki po Europie Aleksandry Olędzkiej-Frybesowej - Choińska, Bogna (Przestrzenie Teorii, 2007)
The article presents a peculiar understanding of religious art, which is possible to be found in Aleksandra Olędzka-Frybesowa's essay writing. An artistic easiness of the usage of symbols is connected with two orders coexistance in a human being: a cosmic and a historical, sacrum and profanum. However, the crisis of European culture (which started together with the fali of Romanesque art) is a result of a separation of these both spheres in a man's consciousness and of a return to Greek-Roman ideals. A recipe for dealing with the crisis within the area of the fine arts is supposedly not regaining early medieval heritage, but rather a humble mimetism. It could constitute an introduction to symbolic generałisation which the author contradicts with abstract thinking.